2006
DOI: 10.1016/j.pbb.2006.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Proximal ethanol pretreatment interferes with acquisition of ethanol-induced conditioned place preference

Abstract: Neurobiological mechanisms underlying rewarding and aversive effects of drugs are often studied by examining effects of various pretreatments on acquisition of conditioned place preference (CPP) or conditioned place aversion (CPA). However, few studies have looked at effects of pretreatment with the same drug used during conditioning. Such studies might offer insight into agonist actions on conditioning while also mimicking real world contingencies experienced by drug users. Previous work from our laboratory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…In accordance with this idea, acute ethanol exposure, which inhibits NMDARs (Lovinger et al, 1989), has been shown to interfere with CPP when administered immediately before conditioning sessions (Cunningham and Gremel, 2006). In contrast, our CPP experiments show that the same repeated ethanol treatment that enhances NMDAR LTP also enhances subsequent learning of cocaine-associated cues.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In accordance with this idea, acute ethanol exposure, which inhibits NMDARs (Lovinger et al, 1989), has been shown to interfere with CPP when administered immediately before conditioning sessions (Cunningham and Gremel, 2006). In contrast, our CPP experiments show that the same repeated ethanol treatment that enhances NMDAR LTP also enhances subsequent learning of cocaine-associated cues.…”
Section: Discussionmentioning
confidence: 93%
“…Both natural rewards and drug rewards, such as ethanol, cause release of dopamine in the nucleus accumbens and other limbic structures, which is thought to drive learning by enhancing synaptic plasticity. However, ethanol intoxication may suppress reward-based conditioning (Busse et al, 2004; Cunningham and Gremel, 2006), presumably by hampering synaptic plasticity in dopamine projection areas (Xie et al, 2009). Accumulating evidence indicates that plasticity of glutamatergic transmission onto dopamine neurons within the VTA may also play important roles in the development of drug addiction (Hyman et al, 2006; Kauer and Malenka, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptations in neuronal architecture of MSN in the Acb following WIN 55,212-2 exposure may contribute to differences in behavior in adolescent versus adult rats in the conditioned place paradigm. As previously reported, conditioned place paradigm is a simple method that offers several advantages including observation of both rewarding and aversive effects (Bardo and Bevins 2000; Cunningham and Gremel 2006; Cunningham et al 2006; Tzschentke 2007). Specifically, conditioned place paradigm offers a choice between the drug-associated cue and a neutral cue (Cunningham et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our laboratory has previously reported many studies showing significant effects of various treatments on the acquisition (Boyce-Rustay & Cunningham, 2004; Chester & Cunningham, 1999; Cunningham & Gremel, 2006a; Gremel & Cunningham, 2008), expression (Bechtholt & Cunningham, 2005; Gremel & Cunningham, 2007, 2008, 2009, 2010) and extinction (e.g., Cunningham et al, 1995, 1998) of EtOH-CPP using the same mouse strain, equipment and procedures described here. Thus, we are confident that the procedures used in the current set of experiments were appropriate for detecting potential effects of SL327 on EtOH-CPP.…”
Section: Discussionmentioning
confidence: 99%